Research on the cloud services provider-oriented services selection method - Yun-yong ZHANG; Su-fen LI; Jun WU; Bing-yi FANG (Tongxin xuebao)
In order to select services more accurately,firstly,a detailed process for services selection was proposed from the perspective of cloud services providers.Secondly,a services selection mathematical programming model was pro-posed for the selection of cloud services by considering two kinds of factors:QoS attributes and services scheduling re-lated parameters,and the model was solved by the GA-based algorithm.Finally,a case study is conducted to demonstrate the feasibility and effectiveness of the proposed approach.